Developing policy-relevant biodiversity indicators: lessons learnt from case studies in Africa - Anne-Julie Rochette; Jean Didier T Akpona; Hugues Adeloui Akpona; Gaston S Akouehou; Blanchard Mayundo Kwezi; Chabi A M S Djagoun; Bernadette Habonimana; Rodrigue Idohou; Ingride S Legba; Benoît Nzigidahera; Augustin Orou Matilo; Mohammed Sghir Taleb; et al. (Environmental Research Letters, 2019)
There is an increasing need for monitoring schemes that help understand the evolution of the global biodiversity crisis and propose solutions for the future. Indicators, including temporal baselines, are crucial to measure the change in biodiversity over time, to evaluate progress towards its conservation and sustainable use and to set conservation priorities. They help design and monitor national and regional policies on biodiversity; they also feed into national reporting on international agreements such as the Convention on Biological Diversity and the Sustainable Development Goals. We analyse the methodological approach of five small African projects resulting from a call to promote indicator development, improve monitoring capacity and strengthen the science-policy interface in the field of biodiversity. We compared their approach to existing guidance provided by the international community, specifically the Biodiversity Indicators Partnership. To this end, we assess whether internationally recommended steps are effectively applied to national/local biodiversity monitoring in selected developing countries. We also present lessons learnt from workshop interactions between partners involved in these projects. Through our pilot projects we identified data availability and data accessibility, together with the involvement of stakeholders, as critical steps in indicator development. Moreover, there is a need for a better awareness and a wider application of the indicator concept itself. Hence, training of key actors both in the policy and science spheres is needed to operationalize indicators and ensure their continuity and sustainability. We hope that these case studies and lessons learnt can stimulate and support countries in the Global South to formulate policy-relevant biodiversity indicators.